Design of highway bridges : an LRFD approach - Barker, R. M. (Richard M.); Puckett, Jay Alan. (Hoboken : Wiley, 2013)
"Here is the updated edition of Wiley's premier reference on the engineering design and analysis of short and medium-span bridges using the Load and Resistance Factor Design (LRFD) methodology. The text has been thoroughly updated throughout to conform with changes made in the latest edition of the AASHTO LRFD Bridge Design Specifications. With content reorganized into smaller and more succinct chapters, coverage also features computer modeling, calibration of service limit states, rigid method system analysis, the green aspects of recycled steel, and concrete shear"--
"Thoroughly updated throughout to conform with changes made in the latest, 5th edition, of the AASHTO LRFD Bridge Design Specifications Content reorganized into smaller and more succinct chapters for ease of use "--
pt. I. General aspects of bridge design -- pt. II. Loads and analysis -- pt. III. Concrete bridges -- pt. IV. Steel bridges.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Bridges -- United States -- Design and construction; Load factor design; TECHNOLOGY & ENGINEERING / Civil / General; Bridges -- Design and construction; Load factor design; Bridges -- United States -- Design and construction; Load factor design; United States; Electronic books; Electronic books